2012
DOI: 10.1097/sap.0b013e31821ee386
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fat Grafting for Correction of Unaesthetic Scars

Abstract: Autologous fat grafting is a good method for correction of retracted or sunken scars instead of the traditional scar surgical excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 15 publications
(7 reference statements)
1
41
0
3
Order By: Relevance
“…39,[45][46][47] The levels of evidence were II in five studies, 33,36,39,41,45 III in seven studies, [23][24][25][26]38,42,44 and IV in 14 studies. 22,23,[28][29][30]32,34,35,37,40,43,[46][47][48] Four randomized controlled trials, 33,36,39,45 16 prospective cohort studies, 22,[25][26][27]29,30,32,34,35,37,38,[41][42][43][44]46 and six retrospective cohort studies …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…39,[45][46][47] The levels of evidence were II in five studies, 33,36,39,41,45 III in seven studies, [23][24][25][26]38,42,44 and IV in 14 studies. 22,23,[28][29][30]32,34,35,37,40,43,[46][47][48] Four randomized controlled trials, 33,36,39,45 16 prospective cohort studies, 22,[25][26][27]29,30,32,34,35,37,38,[41][42][43][44]46 and six retrospective cohort studies …”
Section: Resultsmentioning
confidence: 99%
“…Seven studies showed a statistically significant res ult, [25][26][27]33,41,42,44 and 19 studies did not report any statistical analyses. [22][23][24][28][29][30][31][32][34][35][36][37][38][39][40]43,[45][46][47] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][6][7][8][9][10][11][12][13][14][15][16] Nine of the 15 studies were classified as level IV (case series), two as level III (a retrospective cohort and a comparative clinical study), one as level II (prospective cohort study), and three were not classified (for dealing with animal studies or review articles). No level I studies were found, that is, those with the strongest evidence (controlled and randomized clinical trials).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, autologous fat grafting represents another therapeutic option and has been used on unsightly and retracted scars, 1,2 burn sequelae, 3 and in reconstructive and cosmetic surgeries (to improve body contour, with the intention of filling and increasing volume).…”
mentioning
confidence: 99%